2016
DOI: 10.1021/acsmedchemlett.5b00452
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective CK2 Kinase Inhibitors with Effects on Wnt Pathway Signaling in Vivo

Abstract: ABSTRACT:The Wnt pathway is an evolutionarily conserved and tightly regulated signaling network with important roles in embryonic development and adult tissue regeneration. Impaired Wnt pathway regulation, arising from mutations in Wnt signaling components, such as Axin, APC, and β-catenin, results in uncontrolled cell growth and triggers oncogenesis. To explore the reported link between CK2 kinase activity and Wnt pathway signaling, we sought to identify a potent, selective inhibitor of CK2 suitable for proof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 16 publications
1
83
1
Order By: Relevance
“…CK2 exerts a variety of biological functions, including enhancing growth (18), angiogenesis (19), invasion and metastasis (19,20) in various human tumour xenografts, including lung cancer (19), urothelial cancer (21), mesothelioma (22), hepatocellular cancer (23) and gastric cancer (24), as well as participating in the regulation of different signaling pathways. Previous findings suggested CK2 as a positive regulator of Wnt signaling (25,26); however, to the best of our knowledge, its association with cisplatin resistance in lung cancer cells remains to be elucidated. Previous reports have indicated that the inhibition of dishevelled-2 (DVL-2; the most abundant isoform of the mammalian DVL family) can re-sensitize cisplatin-resistant lung cancer cells by downregulating Wnt/β-catenin signaling (27,28).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…CK2 exerts a variety of biological functions, including enhancing growth (18), angiogenesis (19), invasion and metastasis (19,20) in various human tumour xenografts, including lung cancer (19), urothelial cancer (21), mesothelioma (22), hepatocellular cancer (23) and gastric cancer (24), as well as participating in the regulation of different signaling pathways. Previous findings suggested CK2 as a positive regulator of Wnt signaling (25,26); however, to the best of our knowledge, its association with cisplatin resistance in lung cancer cells remains to be elucidated. Previous reports have indicated that the inhibition of dishevelled-2 (DVL-2; the most abundant isoform of the mammalian DVL family) can re-sensitize cisplatin-resistant lung cancer cells by downregulating Wnt/β-catenin signaling (27,28).…”
Section: Introductionmentioning
confidence: 83%
“…Activation of the Wnt/β-catenin pathway leads to cisplatin resistance in lung cancer (13)(14)(15). Moreover, CK2 is a positive regulator of Wnt signaling (25,26). Therefore, we hypothesized that Wnt signaling might be associated with cisplatin resistance in lung cancer cells; however, the role of CK2 in cisplatin resistance in lung cancer cells, as well as the potential underlying mechanism, remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Even though this class of compounds is the most potent known DAPK1 inhibitors to date, the stability and reactivity issues of the benzylidene‐5‐oxazolone core in biological systems can restrict their use clinically urging for the development of clinically acceptable inhibitors …”
Section: Dapks Inhibitorsmentioning
confidence: 99%
“…We prepared a small library of pyrazolopyrimidines based upon a literature compound that was reported to have DYRK2 activity. 53 We profiled this library using the cell-based DYRK2 nanoBRET assay 68 and we were able to identify AZ-G as meeting the criteria to be named a DK tool for DYRK2 (IC50 = 160 nM). Details about the DYRK2 nanoBRET assay and DK tool can be found at https://darkkinome.org/kinase/DYRK2.…”
Section: Nuak1mentioning
confidence: 99%